The Impact Of Using Trello On Communication and Collaboration In Online Learning Environment - Sinaga, Andromeda Valentino; Sianipar, Rimma (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2025)
This study analyzes the impact of using Trello on students' communication and collaboration in online learning. The data was analyzed descriptively and inferentially using a quantitative method with a survey of 100 students from the Educational Technology Study Program at Universitas Negeri Makassar. The results show that 85% of students are satisfied with Trello in managing tasks, 78% find communication easier through the comment and checklist features, and 80% acknowledge improved team coordination. However, 30% need time to adapt, and 25% still rely on other applications. Additionally, some students stated that Trello’s notification and deadline features help them stay disciplined in completing tasks on time. Overall, using Trello has positively impacted online student collaboration and communication. Nevertheless, training students and lecturers on using Trello is recommended to increase its usefulness further. Additionally, integrating features such as compatibility with video conferencing tools and an improved task notification system should be scheduled to make Trello even more effective for online learning.